Understanding Financing Literacy and Its Impact on Mortgage Application Intention: An Islamic Economics Perspective - Sahid Kelana; Budiana Budiana; Farid Wajdi; Gama Pratama (Ecobankers : Journal of Economy and Banking, 2026)
This study aims to find out whether KPR Artha Graha Surapandan has implemented sharia financing, to determine the level of understanding of the interest in applying for KPR financing at Perum Artha Graha Surapandan and to provide policies on what are the obstacles and what are the solutions to the Understanding Analysis of Financing Interest in submitting mortgages in terms of Islamic Economics. Determine the desired location by conducting research based on data collected from the qualitative framework, qualitative tools, and qualitative data. In this research report, the focus is on an overall picture of the level of consumer understanding of Islamic mortgage financing. Reports come from interview transcripts, field notes, photographs, personal documents, notes or memos, and other official documents. From some of the field findings, it is understandable that all problems can be solved according to the designation of things like this to support the understanding of potential buyers in mortgage financing at Perum Artha Graha Surapan and Cirebon City. Based on the field and correlated with the pillars of terms and buying and selling murabahah such as there are sellers, buyers, products sold, as well as prices and agreements, Perum Artha Graha Surapandan in the application of financing in submitting mortgages is in accordance with the application of sharia. Based on field findings and supported by the DSN-MUI Fatwa regarding murabaha financing. So Perum Artha Graha Surapandan in carrying out sharia mortgage financing is appropriate. So it can be compared to conventional financing, that sharia financing with a murabaha contract allows prospective home buyers to know clear profits and margins and pay installments without being burdened according to the agreed loan period so that mortgage loans can be completed without burden. The obstacle of not passing BI checking is because the prospective buyer has a history of unfinished credit payments, does not have a checking account statement and a permanent job, in this case the developer of Perum Artha Graha Surapan and the City of Cirebon continues to provide solutions by way of sharia financing where prospective buyers can still have a desired house. To increase marketing, you can go through brochures, take part in exhibitions and several agency locations so that interested people have a better understanding of applying for mortgage financing and can be known by many people. As for the problem of financing information from the developer to the buyer, it should be improved again, because it will affect the course of installment payments in making the expected house